EFFECTIVENESS TESTING CREAM OF CASSAVA LEAF ETHANOL EXTRACT (Manihot Usculenta Crantz) ON CONJUSES OF RABBIT (Lepus Negricollis) - Raisah, Putri; Rahmiyani, Dini; Karma, Taufiq (Transpublika Publisher, 2024)
Cassava leaves (Manihot esculenta Crantz) have been clinically studied to contain ingredients such as saponins and flavonoids, which have wound-healing and anti-inflammatory effects. This study aims to determine the effectiveness of cassava leaf (M. esculenta Crantz) ethanol extract cream on bruises in rabbits (Lepus nigricollis). The research is a laboratory experimental study testing the effectiveness of cream preparations with varying concentrations of cassava leaf ethanol extract on bruise healing in rabbits. Cream preparations were made in four formulations: 25%, 50%, 75%, and 100% concentrations. Physical tests of the cream preparations included organoleptic, homogeneity, pH, and spreadability tests. Test animals were divided into treatment and control groups. The treatment group received cream preparations of different concentrations (25%, 50%, 75%, and 100%), while the control group received no treatment. Bruise healing was observed for color changes daily. Physical test results of all cream preparations met the requirements for good cream preparations. In the treatment group, 25% and 50% concentrations showed similar healing processes, with greenish bruises still present on day 14. The 75% and 100% concentrations resulted in the fastest healing, with bruises disappearing and fur regrowth by day 14. The control group's healing process was similar to the 25% and 50% treatment groups. Therefore, the cassava leaf ethanol extract cream was most effective at 75% and 100% concentrations compared to 25% and 50%.